[UAW smoking restrictions] - Susan Stuntz (Tufts Archival Research Center, 2007)
Letter to John Lyons from Susan Stuntz regarding the various smoking policies car manufacturers are adopting. Suggests working more with the UAW and presenting the policies to the labor guys to see what approach they recommend.